2010
DOI: 10.1124/dmd.110.035113
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Ligand-Based Bayesian Model for Human Drug-Induced Liver Injury

Abstract: ABSTRACT:Drug-induced liver injury (DILI) is one of the most important reasons for drug development failure at both preapproval and postapproval stages. There has been increased interest in developing predictive in vivo, in vitro, and in silico models to identify compounds that cause idiosyncratic hepatotoxicity. In the current study, we applied machine learning, a Bayesian modeling method with extended connectivity fingerprints and other interpretable descriptors. The model that was developed and internally v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 47 publications
1
94
0
Order By: Relevance
“…Indeed, in silico models can assist in the prediction of safety of new drug candidates and allow the rapid screening of literately unlimited number of chemicals. Thus, several studies reported the utility of in silico models for the prediction of human hepatotoxicity (Ekins et al 2010;Greene et al 2010;Chen et al 2013b), and recently, Chen et al reported for oral medications at high daily doses and lipophilicity a significant increased risk for clinical DILI as determined by the 'rule-of-two' (RO2, i.e., daily dose ≥100 mg/day & logP ≥ 3) (Chen et al 2013a). While the RO2 model alone added value to the prediction of clinically relevant human hepatotoxicity (Kaplowitz 2013), its performance was still insufficient due to the limited sensitivity caused by a high rate of false negatives.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in silico models can assist in the prediction of safety of new drug candidates and allow the rapid screening of literately unlimited number of chemicals. Thus, several studies reported the utility of in silico models for the prediction of human hepatotoxicity (Ekins et al 2010;Greene et al 2010;Chen et al 2013b), and recently, Chen et al reported for oral medications at high daily doses and lipophilicity a significant increased risk for clinical DILI as determined by the 'rule-of-two' (RO2, i.e., daily dose ≥100 mg/day & logP ≥ 3) (Chen et al 2013a). While the RO2 model alone added value to the prediction of clinically relevant human hepatotoxicity (Kaplowitz 2013), its performance was still insufficient due to the limited sensitivity caused by a high rate of false negatives.…”
Section: Introductionmentioning
confidence: 99%
“…This trend is reflected in predictive models for DILI, most approaches being statistical using different methods (e.g. discriminant analysis [52], Bayesian models [65], artificial neural networks (ANN) [66], k-nearest neighbour quantitative structure--activity relationship (QSAR) [67,68], random forest (RF) [68] or QSAR software [69]), whereas only two published techniques involve developing structural alerts implemented in the knowledge-based expert systems (the Vertex cheminformatics platform (VERDI) [57] and Derek Nexus, formerly Derek for Windows [58]). …”
Section: In Silico Methodologymentioning
confidence: 98%
“…The elevated levels of five liver enzymes, together with a composite module, were chosen to detect hepatotoxic drugs. Another example of a DILI dataset is that of more than 300 drugs and chemicals with a classification scheme based on clinical data of hepatotoxicity [33], later expanded by Ekins et al with a further 237 compounds [65]. Compounds were defined as being DILI positive if they were i) withdrawn from the market due mainly to hepatotoxicity, ii) not marketed in the US due to hepatotoxicity, iii) received black box warnings from the US FDA due to hepatotoxicity, iv) marketed with hepatotoxicity warnings on their labels, v) had well-known associations to liver injury and had a significant number (> 10) of independent clinical reports of serious hepatotoxicity that met the Hy's Law criteria.…”
Section: Currently Available Data For Hepatotoxicitymentioning
confidence: 99%
See 2 more Smart Citations